Identification of Adulterated Evening Primrose Oil Based on GC‐MS and FT‐IR Combined with Chemometrics. Issue 10 (14th September 2022) - Pan, Fengguang; Yang, Enqi; Chen, Xianmao; Li, Peizhi; Wu, Xinling; Zhang, Mingdi
Abstract: Evening primrose oil has a high market value due to its rich unsaturated fatty acids, so it is likely to be adulterated under the drive of economic interests. In this study, evening primrose oil's fatty acid and physicochemical properties are systematically determined, and the characteristic fatty acids are screened out. The feasibilities of GC‐MS and FT‐IR in identifying oil adulteration are also evaluated. Evening primrose oil's major fatty acids are linoleic acid (C18:2), γ‐linolenic acid (C18:3n6), palmitic acid (C16:0), oleic acid (C18:1), and stearic acid (C18:0). In addition, palmitoleic acid (C16:1), hexadecadienoic acid (C16:2), nonadecanoic acid (C19:0), eicosatrienoic acid (C20:3), erucic acid (C22:1), tricosanoic acid (C23:0) and lignoceric acid (C24:0) are rarely detected in other related studies on the evening primrose oil. This study uses fatty acids as indicators, hierarchical cluster analysis, and cosine similarity analysis to identify the evening primrose oil mixed with >5% peanut oil and >10% sunflower oil. Besides, the principal component analysis also distinguishes evening primrose oil blended with different proportions of peanut and sunflower oils. In summary, this study confirms that fatty acids can be characteristic indexes to identify adulterated evening primrose oil by GC‐MS and FT‐IR combined with chemometrics. Practical Applications : This study further clarifies the major and characteristic fatty acids of evening primrose oil. On this basis, the adulteration of evening primrose oil (taking peanut oil and sunflower oil as an example) is identified. Therefore, it is helpful to assess the quality and identify the authenticity of the evening primrose oil, which is vital for the stability of the evening primrose oil market and the interests of consumers. These methods combined with chemometrics can also be extended to ensure the certification of other oils and to classify oils into different classes. The improvements in vegetable oil quality will also benefit the vegetable oil industry and control bodies. Abstract : EPO is expensive due to its high nutritional value, which gives unscrupulous merchants an incentive to profit by adulterating it. The characteristic fatty acids of EPO are clarified by determining physicochemical indexes. Then, GC‐MS and FT‐IR combined with chemometrics (HCA, CSA, and PCA) are used to identify EPO adulterated PO and SO.